Rancang Bangun Aplikasi Rute Pendakian Gunung di Jawa Tengah Terintegrasi Chatbot Berbasis Android - Alkausar, Zidniy Farih; Suhirman, Suhirman (STMIK Banjarbaru, 2024)
Central Java has several famous hiking destinations, such as Mount Prau, Sindoro, Andong, Ungaran and Merbabu. These mountains offer beautiful scenery and are relsatively friendly for beginner climbers. However, the lack of information on climbing routes and the lack of education on the necessary preparations make beginner-friendly mountains very dangerous. Without basic knowledge, climbers will experience difficulties in navigation and be less aware of the terrain and challenges they face. Therefore, this research aims to develop an Android application that provides climbing routes to help climbers navigate, and is equipped with a chatbot feature to provide information and education to climbers. The development method used is the Waterfall Method, with data collection through direct observation, interviews, and documentation studies from official sources. The test results show that this application is effective in helping climbers to find out the climbing route and user position accurately. In addition, the chatbot feature is able to present information and answer simple questions about mountain climbing.Keywords: Android; Chatbot; Navigation; Climber Safety; Mountain ClimbingÂ AbstrakJawa Tengah memiliki beberapa destinasi wisata pendakian terkenal, seperti Gunung Prau, Sindoro, Andong, Ungaran, dan Merbabu. Gunung-gunung tersebut menawarkan pemandangan indah dan relatif ramah untuk pendaki pemula. Namun, kurangnya informasi rute pendakian serta minimnya edukasi persiapan yang diperlukan menjadikan gunung yang ramah pemula menjadi sangat berbahaya. Tanpa adanya pengetahuan dasar, pendaki akan mengalami kesulitan dalam navigasi serta kurang waspada terhadap medan serta tantangan yang dihadapi. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan aplikasi Android yang menyediakan rute pendakian untuk membantu navigasi pendaki, serta dilengkapi fitur chatbot untuk memberikan informasi dan edukasi terhadap pendaki. Metode pengembangan yang digunakan adalah Metode Waterfall, dengan pengumpulan data melalui observasi, wawancara, serta studi dokumentasi. Hasil uji menunjukkan bahwa aplikasi ini efektif dalam membantu pendaki untuk mengetahui rute pendakian serta posisi pengguna secara akurat. Selain itu, fitur chatbot mampu menyajikan informasi dan menjawab pertanyaan sederhana tentang pendakian gunung.Â